Analisis strategi pemberdayaan masyarakat pasca pandemi: studi kasus di indonesia dalam perspektif ekonomi pertahanan - Ivan Yulivan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2022)
The Covid-19 pandemic has had an impact on economic changes in Indonesia. Therefore, this study aims to analyze more deeply related to the post-pandemic community empowerment strategy in the perspective of the defense economy in Indonesia. This study collaborated with ten participants through a qualitative approach. Data collection was carried out with a 95-minute Focus Group Discussion to review data related to post-pandemic economic changes and community empowerment strategies. In-depth interviews were conducted to obtain information related to the planning and development of the post-pandemic defense economy. The interview technique was conducted face-to-face and there were five participants. The interviewees included one community empowerment strategist, two defense economists and two representatives of non-governmental organizations. The duration of time required for in-depth interviews ranges from 65-90 minutes for one participant. The results of this study indicate the process of ratification of community empowerment and economic recovery efforts in Indonesia. In addition, planning and development of the post-pandemic defense economy. This research has implications for community development through processes and actions that can increase community empowerment after the pandemic.